Convenient Cyclopentadiene Modifications for Building Versatile (Radio‐)Metal Cyclopentadienyl Frameworks. Issue 16 (7th April 2021) - Lengacher, Raphael; Braband, Henrik; Csucker, Joshua; Alberto, Roger
Abstract: The synthesis of a bifunctional cyclopentadiene‐based building block, bearing an alkyl linker with a terminal chloride and an ester group is described. This building block was modified by nucleophilic substitution, leading to two new fac ‐[Re(CO)3 ] + containing derivatives of known drug candidates for brain imaging and multi‐drug resistance in cancer in as few as two steps. Furthermore, the chloride was replaced by an azide, which was subsequently coupled to phenylacetylene as a model alkyne to demonstrate its versatility for undergoing Click‐type reactions. The resulting triazole was labelled with 99m Tc to yield the corresponding piano‐stool complex in a radiochemical purity of 86 %. The identities were confirmed by coinjection with the Re homologue. Abstract : The synthesis of [(η 5 ‐C5 H5 ) 99m Tc(CO)3 ] type complexes is tedious and step‐intensive. We herein present a bifunctional cyclopentadiene‐based building block, bearing an alkyl chloride and an ester group. This compound can be functionalized either by nucleophilic substitution or by Click chemistry, allowing the fast and straight‐forward attachment of a cyclopentadiene to biologically interesting moieties with subsequent coordination to Re or 99m Tc.